Implementasi Metode Waterfall Dalam Sistem Aplikasi Money Recording Berbasis Web - Saputri, Indah; Muhammad Dedi Irawan; Muhammad Alfarisi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Deli Serdang District Prosecutor's Branch is a government institution that exercises state power in the field of prosecution and authority. At the Prosecutor's Office, recording expenses is still done manually, so this is less efficient. Therefore, the Deli Serdang District Prosecutor's Office requires an effective and efficient system for financial management. The aim of the research is to simplify web-based financial recording at the Deli Serdang District Prosecutor's Office in order to increase efficiency, transparency and accuracy. In this research, the waterfall method is used. This waterfall method includes the stages of system requirements analysis, system design, implementation, testing and maintenance. The results of the research, namely the output on the report page, prove that the system is running well and the testing stage of the Money Recording Application was carried out using the Black Box testing method. From the test results, the system runs well so that the web-based money recording application can be used.